2021
DOI: 10.1093/femsec/fiab141
|View full text |Cite
|
Sign up to set email alerts
|

Experimental test of microbiome protection across pathogen doses reveals importance of resident microbiome composition

Abstract: The commensal microbes inhabiting a host tissue can interact with invading pathogens and host physiology in ways that alter pathogen growth and disease manifestation. Prior work in house finches (Haemorhous mexicanus) found that resident ocular microbiomes were protective against conjunctival infection and disease caused by a relatively high dose of Mycoplasma gallisepticum (MG). Here, we used wild-caught house finches to experimentally examine whether protective effects of the resident ocular microbiome vary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 81 publications
0
15
1
Order By: Relevance
“…eye inflammation) than females (Adelman et al, 2015; Hawley et al, 2007; Moyers et al, 2018). However, the evidence is inconsistent as some studies have found greater pathology in females (Altizer et al, 2004; Leon & Hawley, 2017) and many find no difference between sexes (Sydenstricker et al, 2006; Thomason et al, 2017; Vinkler et al, 2018; Weitzman et al, 2021). Robust studies explicitly testing for sex-biased resistance in house finch populations are lacking and needed to better understand these dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…eye inflammation) than females (Adelman et al, 2015; Hawley et al, 2007; Moyers et al, 2018). However, the evidence is inconsistent as some studies have found greater pathology in females (Altizer et al, 2004; Leon & Hawley, 2017) and many find no difference between sexes (Sydenstricker et al, 2006; Thomason et al, 2017; Vinkler et al, 2018; Weitzman et al, 2021). Robust studies explicitly testing for sex-biased resistance in house finch populations are lacking and needed to better understand these dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while there is limited data available on sex-biased differences in MG pathology, we were able to find three studies that found sex-biased pathology in house finches that is similar to our findings in canaries (Adelman et al, 2015; Hawley et al, 2007; Moyers et al, 2018). However, this pattern is inconsistent as there were many that found no difference between sexes (Sydenstricker et al, 2006; Thomason et al, 2017; Vinkler et al, 2018; Weitzman et al, 2021) and a couple that found higher female pathology in house finches (Altizer et al, 2004; Leon & Hawley, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…As part of a separate study (Weitzman et al 2021), birds were assigned to one of three MG treatment groups: a high (3×10 4 color-changing units/mL, CCU/mL; n =11) or medium (3×10 3 CCU/mL, n =12) dose of MG, or sham control treatment with sterile media ( n =10). Birds were inoculated with 70 µL total (approximately 35 µL/eye) by droplet installation into the conjunctiva with either Frey's medium alone (control treatment) or the VA1994 MG isolate (7994-1 6 P 9/17/2018) diluted in Frey's medium to the appropriate concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Birds were inoculated with 70 lL total (approximately 35 lL/ eye) by droplet installation into the conjunctiva with either Frey's medium alone (control treatment) or the VA1994 MG isolate (7994-1 6 P 9/17/ 2018) diluted in Frey's medium to the appropriate concentration. Because of the large number of birds in the associated study (Weitzman et al 2021), birds were divided temporally into two groups that were inoculated and sampled 4 wk apart but otherwise treated identically. Both temporal groups included birds in all experimental treatments.…”
Section: Experimental Design Inoculation and Data Collectionmentioning
confidence: 99%
“…For cloacal swab bacterial community assessment, we amplified the V4 region of bacterial 16S rRNA gene with the 515F/806R primers ( Caporaso et al, 2012 ) as previously described ( Thomason et al, 2017 ; Hernandez et al, 2020 ; Weitzman et al, 2021 ), and amplicons were sequenced using a 250 bp single-end strategy on an Illumina MiSeq at the Dana Farber Cancer Center of Harvard University. Forward reads were demultiplexed in QIIME2 ( Bolyen et al, 2019 ) and processed with the DADA2 package with R version 4.0.2 in RStudio version 1.3.1093 ( R Development Core Team, 2015 ; Callahan et al, 2016 ; RStudioTeam, 2020 )).…”
Section: Methodsmentioning
confidence: 99%